Optimizing the Utilization of Swamp Lands for Urban Settlements in Kertapati District, Palembang - Maulana Yusuf; Nurhayati Damiri; Ardiyan Saptawan; Syafrul Yunardy; Nur Aslamiah Supli (Program Pascasarjana Universitas Sriwijaya, 2023)
The water crisis caused by floods and droughts has become an urgent problem in many regions worldwide. To address these challenges, the provision of empty spaces for rainwater harvesting has been a focus of attention as a potential solution to reduce the adverse impacts of these extreme phenomena. The objective of this study is to explore and propose effective strategies for optimizing the utilization of swamp lands for urban settlements in the Kertapati District of Palembang. The research methodology involves quantitative and qualitative analyses of hydrological data and land use on a property in Bukit Lama IB I, Palembang, South Sumatra, who has implemented the rainwater harvesting system. The hydrological data includes rainfall, roof catchment area, yard area, and rainwater accumulation rates. The results of the study show that the provision of empty spaces for rainwater harvesting can significantly reduce the risks of floods and droughts. When heavy rainfall occurs, this system can retain excess rainwater, thereby reducing surface runoff volume and slowing the flow towards rivers. Additionally, the harvested water can serve as a reserve to cope with drought during the dry season. The research also identifies several critical factors influencing the effectiveness of the rainwater harvesting system, including infrastructure design and surrounding land use. In this context, collaboration between the government, communities, and the private sector becomes crucial in implementing this system widely and sustainably. In conclusion, the provision of empty spaces for rainwater harvesting has proven to be an effective approach in reducing the risks of floods and droughts. Facing increasingly complex climate change, it is essential for communities, governments, and other stakeholders to adopt and implement this system as part of a comprehensive strategy to manage water resources sustainably and protect the environment.